ANALISIS PEMBANGUNAN CANAL BLOCKING SEBAGAI SOLUSI PENCEGAHAN KEBAKARAN LAHAN GAMBUT DI DESA SUNGAITOHOR KABUPATEN KEPULAUAN MERANTI - Nova Erlina; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Land and forest fires in indonesia was happened since 1982 and 1983. Which has adverse impacts and very harmful in various aspects specially the due of haze A fire was difficult switched off and many mog because of wildfire occured in peat land which of peat have an characteristics porous was caused the wildfire not only on surface but also in ground fire. Peat land should be wet and resistant to wildfire. However, many canals was built above cause water drained whithout under control so that peat was became dried up in summer and flammable. Therefore, should be done isolation on canal blocking.This reserach is aimed to know and analyze canal blocking development as solution wildfire prevention peatland and to know influencing factors canal blocking development in Sungaitohor Village Kepulauan Meranti district. This research was built by using concept of management theory by Luther Gullick. The method used in this study is qualitativ approach explorative. Data analysis was used with interview, observation and documentation.The research found that canal blocking development as solution widfire prevention in Sungaitohor village Kepulauan Meranti district was good and can be said successfull. The evidenced by the decrease of fire hotspots even in 2016 there was no spot of fire in Sungaitohor Village. Influencing factor canal blocking development in Sungaitohor village is society partisipation and the local wisdom society toward peat.key word: management, canal blocking, land and forest fires, peat